Hengellistä, sosiaalista ja kansallista huolenpitoa : Suomen evankelisluterilaisen kirkon järjestämä suomenkielinen kirkollinen toiminta Ruotsissa 1945 - 1967 - Rohkimainen, Päivi (Helsingin yliopisto, 2014)
The main purpose of this study was to find out motives of the Lutheran Church of Finland for its activities in Sweden during years 1945-1967. Work as itself was made by a national ecclesiastical organization Suomen kirkon seurakuntatyön keskusliitto (SKSK). Church of Sweden had already organized activities for Finnish speaking inhabitants especially in northern Sweden. It also had a Finnish congregation in Stockholm. The main sources for the study were the archives of the Diaspora committee of the SKSK which are located in the National Archive of Finland and the in Unit for Ministry to Finns Abroad, which is under the Department of International Relations of Lutheran Church of Finland. During 1945-1949 the Diaspora committee sent pastor Aarne Siirala to Stockholm to organize all kinds of help from Sweden to Finland. The other task for him was to serve as a Finnish speaking pastor among Finns in Stockholm and nearby. He had time only for the charitable duties. And when fundraising collapsed because of some malpractices, pastor Siirala moved back to Finland. Year 1947 Finnish pastor Yrjö Knuutila got a short message from Sweden. The message was sent by an Ingrian, who wanted to get some Lutheran spiritual guidance to Borås where they lived. Political situation in Finland was very vulnerable because of the cautious relationship with Soviet Union. Knuutila discussed with SKSK s General Secretary Toivo Laitinen what to do. They had both participated the Winter war and the Continuation war and were members of a new theological movement Asevelipapit. This new group believed that that the Lutheran Church should take part to everyday life and follow brothers wherever they go. Knuutila and Laitinen descided to act. They organized Finnish pastors to travel to Sweden to give a finnish sermon to Ingrians. In 1950 s immigration from Finland to Sweden increased. The consequences were of many kinds. First most of the Finns stayed in Stockholm and its neighboring area and later even western and southern parts of Sweden. The ...